Beluga (D. leucas), harbor porpoise (P. phocoena), and killer whale (O. orca) acoustic presence in kotzebue sound, alaska: Silence speaks volumes - Castellote, Manuel; Small, Robert J.; Stafford, Kathleen M.; Whiting, Alex; Frost, Kathryn J. (Frontiers in Remote Sensing, 2022)
Prior to 1984, belugas (Delphinapterus leucas) were seen in large numbers in Kotzebue Sound, Alaska, during spring and summer and provided an important subsistence resource to coastal residents. Sightings and harvest declined sharply beginning in 1984: the average annual harvest dropped from 84/yr (1977-1983) to 16/yr (1984-2021). To examine this shift in beluga presence, passive acoustic moorings were deployed in summer 2013 and year-round in 2014-2016, to describe the seasonal and geographic occurrence of belugas. Three moorings were deployed off Cape Krusenstern, northwestern Kotzebue Sound, to monitor cetaceans traveling nearshore. A mooring was also deployed near Chamisso Island, southeastern Kotzebue Sound. We used automatic detectors to process the recordings for echolocation and tonal signals, and all detections were manually validated. Belugas, harbor porpoises (Phocoena phocoena), and transient killer whales (Orcinus orca) were detected in both areas, primarily from June to November. Detections extended into early winter for belugas, and sporadic detections were confirmed for porpoises from January to March. Belugas were detected on a total of 20 days, killer whales on 96 days, and porpoises on 179 days. The only beluga detections were echolocation signals. The absence of social signals likely reflects an anti-predator response to the presence of hunters and transient killer whales. Killer whale detections were composed of echolocation signals, limited to very short click trains, double clicks, and single clicks, a known cryptic acoustic behavior used when targeting prey. Killer whales also emitted high frequency whistles (17-51 kHz) providing the first evidence of this type of signals for transients. Our results suggest transient killer whales in predation mode scouting typical beluga habitat, concurrent with belugas in silent anti-predation mode. This anti-predation acoustic behavior was also evident outside the killer whale season, conveying a continued perception of predation risk for this habitat. If the increase in transient killer whale presence in Arctic waters is also taking place in Kotzebue Sound, the combined natural and anthropogenic predation pressure sustained by this habitat could be playing an important role in the continued low occurrence of beluga, with a consequent impact to the subsistence communities that rely on this species.